Epidendrum tolimense Lindl. (Orchidaceae), una especie sudamericana encontrada en Costa Rica - Hágsater, Eric (2016)
A species previously known from South America is found in the Cordillera de Talamanca, Costa Rica. Epidendrum tolimense belongs to the Elleanthoides Group, and is the first species of this group to be found outside the Andes.